Reductionism in contemporary philosophy of causation - Grenda, Vytautas (Problemos, 2012)
This paper provides an overview of how the term “reduction” is used in contemporary philosophy of causation. It is considered how, according to this usage, theories of causation may be classified as reductive or as non-reductive, and what types of reductive theories may be distinguished. On the basis of this metatheoretical analysis, the prospects of two forms of reductionism, namely, so-called “Humean reductionism” and “empirical analysis”, are evaluated.